2006
DOI: 10.1038/sj.ejcn.1602485
|View full text |Cite
|
Sign up to set email alerts
|

The total antioxidant capacity of the diet is an independent predictor of plasma β-carotene

Abstract: Objective: To investigate the contribution of the total antioxidant capacity (TAC) of the diet to plasma concentrations of b-carotene. Design: Cross-sectional study. Setting: Department of Public Health and Department of Internal Medicine and Biomedical Sciences, University of Parma. Subjects: A total of 247 apparently healthy adult men (n ¼ 140) and women (n ¼ 107). Methods: A medical history, a physical exam including height, weight, waist circumference and blood pressure measurements, a fasting blood draw, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 44 publications
4
22
0
1
Order By: Relevance
“…The present intervention confirms the previous cross-sectional observation that the TAC of the diet is an important determinant of plasma b-carotene concentrations regardless of b-carotene intake (Valtueña et al, 2007).…”
Section: Wo Lt Htsupporting
confidence: 91%
See 1 more Smart Citation
“…The present intervention confirms the previous cross-sectional observation that the TAC of the diet is an important determinant of plasma b-carotene concentrations regardless of b-carotene intake (Valtueña et al, 2007).…”
Section: Wo Lt Htsupporting
confidence: 91%
“…Total antioxidant capacity (TAC) of the diet, which describes the ability of the different antioxidants (independent of their bioavailability) present in food and beverages in scavenging preformed free radicals, was strongly associated to higher plasma concentrations of b-carotene in free living participants, independent of b-carotene intake, and other relevant dietary and clinical confounders (Valtueña et al, 2007). To confirm this observation, we conducted a cross-over intervention study investigating the extent of changes in circulating carotenoids (and particularly b-carotene) as result of two dietary strategies designed to be quantitatively comparable in b-carotene, fruits, vegetables, dietary fibre and alcohol intake, but remarkably different regarding their TAC content.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, DQIR has been associated with circulating b-carotene, among other plasma antioxidants, in men [2]. In this sense, dietary TAC has been related to prediction of circulating levels of b-carotene [47]. The association between dietary TAC and Mediterranean hypothesis-oriented dietary scores could thus be explained by the assumed features of the Mediterranean dietary pattern, which combines abundant plant foods (fruits, vegetables, cereals, nuts, seeds, wine, and olive oil) with a large potential amount of active dietary antioxidants [48].…”
Section: Discussionmentioning
confidence: 95%
“…The recently developed concept of total dietary antioxidant capacity (Brighenti et al, 2005) overcomes this limitation by summarizing the capacity of different food antioxidants in scavenging free radicals. Indeed, existing studies have revealed an inverse association of total dietary antioxidant capacity with C-reactive protein (CRP) (Brighenti et al, 2005), gastric cancer (Serafini et al, 2002) and total mortality (Agudo et al, 2007), as well as a positive relation with plasma b-carotene (Brighenti et al, 2005;Valtuena et al, 2007), which substantiates the value of this new dietary variable as a useful tool for the investigation of diet-disease relations in the epidemiological field.…”
Section: Introductionmentioning
confidence: 88%